"What Stood Out was How Much Pressure the System had Been Under". Issue 5 (29th September 2021) - Tarran, Brian
Abstract: Siobhan Tuohy-Smith and Ed Humpherson discuss the state of the UK statistical system, its response to the demands of Covid, and preparing for what comes next. Interview by Brian Tarran